VDR gene polymorphism in susceptibility to urolithiasis among the Asian population: A systematic review and meta-analysis - Yumnam, Malvika; Sanjenbam, Yaiphaba (Anthropological Review, 2024)
Urolithiasis is one of the most prevalent urinary diseases worldwide. Several studies have reported VDR gene polymorphisms to have a contributing genetic factor in susceptibility to urolithiasis and suggested its possibility of being a good candidate marker for urolithiasis. However, results across numerous studies centred on the relationship between the VDR gene polymorphism and urolithiasis have been inconclusive. To perform a meta-analysis concerning the association between the risk of urolithiasis and VDR gene polymorphismsviz., ApaI, BsmI, FokI, and TaqI among the Asian population. A comprehensive electronic search was conducted to identify published studies that investigates the relationship between four polymorphisms (ApaI, BsmI, FokI and TaqI) in the VDR gene and the risk of urinary stone disease using electronic databases. VDR ApaI and FokI polymorphisms were found to be associated with urolithiasis risk. Results from pooled analysis indicated ApaI aa genotype to be associated with urolithiasis compared to AA or Aa genotypes. In addition, the minor f allele of FokI variant was identified to be the risk allele in susceptibility to urolithiasis while F allele to be protective. Moreover, from the subgroup analysis, the ff genotype of FokI and aa genotype of ApaI were associated with higher risk of urolithiasis among the East Asian but not among the Southwest Asians.